(untitled) (Research, Society and Development, 2024)
Objective: Review and critically analyze the main innovations in glass ionomer cement formulations, identifying trends and future challenges for their clinical application. Methodology: A narrative review was conducted, utilizing databases such as Google Scholar, SciELO, Cochrane, and PubMed. Scientific articles from the last 15 years, in Portuguese and English, addressing innovations in glass ionomer cements, were selected. Inclusion and exclusion criteria were rigorously applied to ensure the relevance of the studies analyzed. Results and Discussion: The results indicated that the use of nanoparticles, resins, and bioactive materials have significantly contributed to improving the properties of glass ionomer cements. However, the scarcity of clinical trials and the diversity in methodologies used in the reviewed studies limit the generalizability of the conclusions. The discussion emphasizes the need for more clinical research to validate laboratory innovations and explore combinations of materials that may offer even more effective solutions. Conclusion: Innovations in glass ionomer cements show considerable potential to transform dental practice, promoting more durable and accessible treatments.